Multi-disciplinary computational investigations on asymmetrical failure factors of disc brakes for various CFRP materials: a validated approach - Raja, Vijayanandh; Gnanasekaran, Raj Kumar; Kaladgi, Abdul Razak; Rajendran, Parvathy; Khan, Sher Afghan; Asif, Mohammad (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Finite element analyses (FEA) are flexible and advanced approaches, which are utilized to address difficult problems of aerospace materials that exhibit both structural symmetrical and structural asymmetrical characteristics. Frictional behavior effects are used as a crucial element in this multidisciplinary study, and other structural, and thermal properties are computed using FEA. Primary lightweight materials such as glass fiber reinforced polymer (GFRP), carbon fiber reinforced polymer (CFRP), Kevlar fiber reinforced polymer (KFRP), titanium alloy, tungsten carbide, steel alloys, and advanced lightweight materials, such as silicon carbide (SiC) mixer, based on aforesaid materials underwent comprehensive investigations on an aircraft disc brake, two-wheeler disc brake, and ASTM general rotating test specimen (G-99). Standard boundary conditions, computational sensitivity tests, and theoretical validations were conducted because the working nature of FEA may impair output dependability. First, FEA calculations were performed on a standard rotating disc component with two separate material families at various rotational velocities such as 400 RPM, 500 RPM, 600 RPM, 800 RPM, and 10 N of external frictional force. Via tribological experiments, frictional force and deformation of FEA outcomes were validated; the experimental outcomes serve as important boundary conditions for real-time simulations. Second, verified FEA was extended to complicated real-time applications such as aircraft disc brakes and automobile disc brakes. This work confirms that composite materials possess superior properties to conventional alloys for aircraft and vehicle disc brakes.